THE INFLUENCE OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE JOB SATISFACTION IN THE YOROZU AUTOMOTIVE INDONESIA COMPANY - Andini; Aji Tuhagana; Zenita Apriani (Journal Of Resource Management, Economics And Business, 2024)
Purpose: This study aims to determine the influence of compensation and work motivation on employee job satisfaction at PT Yorozu Automotive Indonesia. Research Methodology: The study used a questionnaire as the instrument and a sample of 64 employees. Associative research was employed to understand the influence between the independent and dependent variables through multiple linear regression. Results: The results show that compensation has a positive influence on employee job satisfaction, work motivation has a positive influence on employee job satisfaction, and both compensation and work motivation have a positive influence on employee job satisfaction. Limitations: The study was limited to PT Yorozu Automotive Indonesia, and the findings may not be generalizable to other organizations. Contribution: The findings of this study can be useful for human resource management, particularly in the automotive industry, to understand the importance of compensation and work motivation in enhancing employee job satisfaction.